Expression of C1q by Macrophages and Fibroblasts in Tumor Microenvironment Is Associated with Progression and Metastasis of Cutaneous Squamous Cell Carcinoma - Viiklepp, Kristina; Knuutila, Jaakko S.; Nissinen, Liisa; Siljamäki, Elina; Rappu, Pekka; Suwal, Ujjwal; Pellinen, Teijo; Kallajoki, Markku; Meri, Seppo; Heino, Jyrki; Kähäri, Veli-Matti; Riihilä, Pilvi (Elsevier BV, 2026)
Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer, with poor prognosis for metastatic cases. We demonstrated previously that cSCC cells in culture express C1r and C1s components of the complement C1qr2s2 complex but not C1q. In this study, significantly higher mRNA levels of C1QA, C1QB, and C1QC variants 1 and 2 were found in cSCC tumors than in normal skin. Analysis of single-cell RNA-sequencing data of cSCC revealed expression of mRNAs for C1QA, C1QB, and C1QC in macrophages and activated fibroblasts. C1q staining was detected on the surface of cSCC tumor cells, in peritumoral and intratumoral macrophages, and in peritumoral activated fibroblasts using immunohistochemistry and multiplexed immunofluorescence. Expression was higher in cSCCs than in normal skin, actinic keratoses, and cSCC in situ. C1q production was induced in 3-dimensional spheroid cocultures of cSCC cells, fibroblasts, and macrophages. C1q stimulated the growth of cSCC cells in culture. C1q expression was significantly more prevalent in metastatic primary cSCCs and in metastases than in non-metastatic cSCCs. High C1q expression in cSCC correlated with poor prognosis. These findings provide evidence for macrophage- and fibroblast-derived C1q in the progression of cSCC. They also suggest stromal C1q as a marker for cSCC metastasis and poor prognosis.